Qui enquête (sur) qui ? - Océane Sipan (Socio-anthropologie, 2022)
Successive lockdowns have raised the question of how to remotely conduct fieldwork? This article looks back at this issue by drawing on three remote fieldwork experiences. Even before the covid crisis, the online fieldwork had become a way of distancing oneself and continuing research despite a researcher’s aversion towards her informants. After the health restrictions, two surveys were set up, delegating the production and collection of data to the participants who had become auto-ethnographers. The article discusses the methodological and ethical choices that shaped these innovative fieldwork arrangements and looks at what distance does to the relationship between the informants and the researcher and to the data collected. Although they fail to document the routine of their ecological practices, the initial object of the survey, the heterogeneous data remotely collected prove to be heuristic when analysed through the prism of their conditions of production.